Iqbal's theory of personality: a contrastive analysis with Freud - Abdul Razak, Mohd Abbas (2014)
This study in the area of philosophical psychology is a contrastive analysis on the personality theories that have been showcased to the world by Freud and Iqbal. In analyzing the data pertinent to the study, the researcher has used the historical and content analysis methods. As a prelude to the kernel of the research, the researcher has explored the historical and philosophical developments that have taken place in the areas of human nature and personality in the West and Islamic world. The fact that both Iqbal and Freud believed the inner dimension of man, particularly the ego, which plays a pivotal role in all human behaviors has drawn the interest of the researcher to explore their concepts on the human psyche, and on how personality development takes place in individuals. Through the contrastive analysis, it has come to light that Freud and Iqbal had conceptualized their theories on personality as a response to the demands and challenges of their time. Besides that, factors like their personality, philosophy towards life, education and their travels have influenced directly or indirectly their conceptualization of their theories